'Our Pier': leisure activities and local communities at the British seaside. Issue 2 (3rd April 2019) - Brydon, Lavinia; Jenzen, Olu; Nourse, Nicholas
ABSTRACT: The seaside resort has long held a distinctive position within the history of British leisure. Its peculiar physicality whereby the natural landscape of sea and sand combines with distinctive architectural elements, such as pavilions and piers, has accommodated many and varied leisure activities across the years. However, to date, the majority of research on British coastal resorts considers these activities solely in connection with tourism. Using a combination of contextual archival research, participant observations, semi-structured interviews and oral history narratives, this article attempts a deliberate shift in focus where the leisure activities of a young local population are brought to the fore in the history of British seaside entertainment and, in particular, their experiences of pleasure piers in the post-war era. The article also explores the potential for the concept of the 'community pier' in terms of nurturing seaside leisure cultures in the present and future.